Modelling and Torque Tracking Control of Permanent Magnet Synchronous Motor For Hybrid Electric Vehicles - Rahmat, Mohd Sabirin; Ahmad, Fauzi; Mat Yamin, Ahmad Kamal; Aparow, Vimal Rau; Tamaldin, Noreffendy (UMP Publisher, 2013)
This paper presents a detailed derivation of a permanent magnet synchronous motor, which may be used as the electric power train for the simulation of a hybrid electric vehicle. A torque tracking control of the permanent magnet synchronous motor is developed by using an adaptive proportional-integral-derivative controller. Several tests such as step function, saw tooth function, sine wave function and square wave function were used in order to examine the performance of the proposed control structure. The effectiveness of the proposed controller was verified and compared with the same system under a PID controller and the desired control. The result of the observations shows that the proposed control structure proves to be effective in tracking the desired torque with a good response. The findings of this study will be considered in the design, optimisation and experimentation of series hybrid electric vehicle.